Systematic Literature Review: Developing Gamification to Enhance Elementary School Students' Learning Outcomes - Agnes Clarissa Panjaitan; Panca Dewi; Bambang Subali; Arif Widiyatmoko (FKIP - Universitas Riau, 2026)
The development of gamification as a learning media is essential to provide primary school students with a contextual, motivating learning experience that can enhance their learning outcomes. Despite its potential, research on the integration of gamification in improving learning outcomes at the primary education level remains limited. Therefore, a comprehensive literature review is necessary to identify current trends, challenges, and future opportunities for development in this area. This study aims to explore how gamification can improve critical thinking skills among primary school students from 2021 to 2025 by employing the Systematic Literature Review (SLR) method. The analysis of 18 research papers demonstrated that gamification strategies significantly improve students' learning outcomes. Furthermore, gamification not only enhances academic performance but also strengthens cognitive, affective, and social dimensions by boosting students’ motivation, creativity, and meaningful engagement in the learning process. These findings suggest that implementing gamified learning media can play a crucial role in fostering a more effective and holistic education for young learners.